Aerobic granular processes: Current research trends. (June 2016) - Zhang, Quanguo; Hu, Jianjun; Lee, Duu-Jong
Highlights: Recent R&D works for aerobic granular process were reviewed. Treatments, granulation mechanisms and stability, and waste reuse were covered. Challenge and prospect for commercialization of aerobic granular process were discussed. Abstract: Aerobic granules are large biological aggregates with compact interiors that can be used in efficient wastewater treatment. This mini-review presents new researches on the development of aerobic granular processes, extended treatments for complicated pollutants, granulation mechanisms and enhancements of granule stability in long-term operation or storage, and the reuse of waste biomass as renewable resources. A discussion on the challenges of, and prospects for, the commercialization of aerobic granular process is provided.